2015
DOI: 10.1136/bmjopen-2014-006577
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomised trial of cloth masks compared with medical masks in healthcare workers

Abstract: ObjectiveThe aim of this study was to compare the efficacy of cloth masks to medical masks in hospital healthcare workers (HCWs). The null hypothesis is that there is no difference between medical masks and cloth masks.Setting14 secondary-level/tertiary-level hospitals in Hanoi, Vietnam.Participants1607 hospital HCWs aged ≥18 years working full-time in selected high-risk wards.InterventionHospital wards were randomised to: medical masks, cloth masks or a control group (usual practice, which included mask weari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
522
0
26

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(556 citation statements)
references
References 33 publications
8
522
0
26
Order By: Relevance
“…25 Similarly, in non-MG settings, effectiveness of facemask varied depending on the study endpoint. [42][43][44][45][46][47][48][49][50][51][52][72][73][74] Metaanalysis of RCTs involving facemask in non-MGs showed efficacy against ILI but not against laboratory-confirmed influenza. 14,15,75 This study is the first focussed systematic review that describes both the uptake and effectiveness of facemasks against respiratory infections in MGs, and it compiles a data pool of 12710 participants originating from more than 50 countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Similarly, in non-MG settings, effectiveness of facemask varied depending on the study endpoint. [42][43][44][45][46][47][48][49][50][51][52][72][73][74] Metaanalysis of RCTs involving facemask in non-MGs showed efficacy against ILI but not against laboratory-confirmed influenza. 14,15,75 This study is the first focussed systematic review that describes both the uptake and effectiveness of facemasks against respiratory infections in MGs, and it compiles a data pool of 12710 participants originating from more than 50 countries.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the uptake of facemask among HCWs in several studies ranged from 56.6% to 84.3% (average 70.7%). [42][43][44][45] On the other hand, the uptake of facemask among ordinary population in diverse household and community settings ranged from 38% to 80.7% (average 55%). [46][47][48][49][50][51][52] This could be explained by several individual or organisational factors.…”
Section: Discussionmentioning
confidence: 99%
“…Another unique finding to emerge from our study was that female pilgrims preferred to use a niqab (face veil) instead of a facemask because the niqab is more comfortable and breathable. This has potential public health importance, as a recently published randomized trial identified that cloth masks actually increase the risk of ILI [25].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized clinical trial found that medical staff members who used a mask correctly had a decrease in virus transmission (MacIntyre et al, 2015). Although less is known about the efficacy of wearing a mask in community settings, wearing a mask showed efficacy in young adults (Aiello et al, 2010b, Aiello et al, 2012).…”
Section: Discussionmentioning
confidence: 99%